“Pacaran, Yuk!”: Sebuah Studi Kasus Mengenai Proses Percintaan di LINE PLAY, Our Avatar World - Nabila Anggana Laras (Antropologi Indonesia, 2021)
This article will explain about the love process of the players that occurs in a chat-based online game called LINE PLAY - Our Avatar World. LINE PLAY is an online game that aims to interact by bringing a player closer to another player who is distant and foreign, including virtual dating. The case studies are taken from virtual dating experiences carried out by LINE PLAY players whom are members of a “BROTHERHOOD” group, namely, Momo, Sapi, Rio, and Emeng. They were represented by an avatar in the LINE PLAY world. This research was conducted online and offline for 1 year and 2 months. In Online data research, my avatar, Volans and I conducted participatory observations and interviews to get to know the respondents in LINE PLAY. In Offline data research, I met the respondents in real life by conducting interviews in Dago, Bandung, West Java. In this research, I found that LINE PLAY as a virtual space is a serial world for someone which doing a virtual dating. That is, when players date virtually, there are many options for virtual spaces that are similar to the steps of someone who takes in finding a girlfriend in the real world. So, it becomes an imitation for a player to look for a girlfriend virtually. Also, LINE PLAY is also an extension of a player in virtual dating, represented by an expansive, playful avatar that makes it interesting to play.